Piloting Group-Based Behavioral Activation Therapy for Families of Deceased COVID-19 Patients - Ashley Eaton England, MA; Stephanie Lietzau, BS; James Vu, BS; Charles Hebert, MD; David Banayan, MD; Jared A. Greenberg, MD; James Gerhart, PhD (Critical Care Explorations, 2022)
BACKGROUND:. Surrogate decision-making is a stressful process for many family members of critically ill patients. The COVID-19 pandemic may have amplified the risk for anxiety, depression, and posttraumatic stress disorder (PTSD) symptoms in ICU surrogates. OBJECTIVES:. This study piloted an online group-based behavioral intervention with family members of deceased COVID-19 patients. Participant engagement, perceptions, and responses related to the intervention were assessed. DESIGN:. A single-arm pilot study was conducted with bereaved families. Quantitative analysis of measures of anxiety, depression, and PTSD symptoms was conducted with mixed models. Qualitative data were analyzed to identify themes in surrogates’ experiences with the intervention. SETTING:. Participants were recruited from ICUs at a tertiary academic medical center. Participants completed the intervention, measures, and interviews online. SUBJECTS:. Participants were family members of patients who died from COVID-19. INTERVENTIONS:. The intervention involved six online group-based behavioral activation sessions. Sessions covered topics pertinent to grieving and engagement in personally meaningful activities. MEASUREMENTS AND MAIN RESULTS:. Semi-structured interviews explored participants’ experiences with the intervention. Surrogates also completed measures of anxiety, depression, and PTSD symptoms before and after the intervention. Nineteen of 26 participants (73.1%) completed the study. Thematic analysis suggested that surrogates found the group helpful for overcoming perceived isolation, receiving validation, and developing coping skills. Significant pre-to-post reductions were observed in symptoms of Hospital and Anxiety Disorder Scale (HADS) anxiety (pre-mean = 9.27, sd = 5.30 vs post-mean = 6.80, sd = 4.16; p = 0.0271), HADS depression (pre-mean =6 .65, sd = 4.58 vs post- mean = 4.89, sd = 3.40; p = 0.0436), and Impact of Events Scale-Revised PTSD (pre-mean = 36.86, sd = 16.97 vs post-mean = 24.14, sd = 13.49; p = 0.0008). LIMITATIONS:. This was a preliminary study based on qualitative and self-report measures. Future studies should include a control group. CONCLUSIONS:. Online group-based behavioral activation therapy appears to be a potentially useful intervention for family members of ICU patients who died from COVID-19.